Dynamic change of IDO1 activity predicts survival in patients with unresectable stage III NSCLC and chemoradiotherapy - Wu, Linfang; Wang, Daquan; Chen, Yanhua; Qian, Mingmin; Xu, Xin; Zhang, Tao; Bi, Nan; Wang, Luhua (Frontiers in Immunology, 2022)
Objectives: High activity of Indoleamine 2,3-dioxygenase1 (IDO1) in lung cancer patients converts tryptophan (Trp), which is the essential amino acid for T cell metabolism, to kynurenine (Kyn) and consequently suppresses anti-tumor immune responses. We aimed to track the dynamics of IDO1 activity in stage III non-small cell lung cancer (NSCLC) patients who received first-line radiotherapy (RT) and explore its association with survival outcomes. Materials and Methods: Systemic IDO1 activity was calculated by Kyn:Trp ratio. Plasma levels of Kyn and Trp in 113 thoracic RT-received stage III NSCLC patients were measured by high-performance liquid chromatography before the initiation of RT. Dynamic change of IDO1 activity was followed in 24 patients by measuring Kyn:Trp ratio before, during and after RT administration. Results: In 24 patients with dynamic tracking of plasma IDO1 activity, there was no significant alterations observed among the three time points (Friedman test, p=0.13). The changing pattern of Kyn:Trp ratio was divided into four groups: decreased consistently during RT, first increased then decreased, increased consistently, first decreased then increased. Patients whose Kyn:Trp ratio kept decreasing or first increased then decreased were defined as good-change group. The good-change status was identified as an independent positive factor for overall survival (OS) and progression-free survival (PFS) (p=0.04; p=0.01) in multivariate analysis among evaluated parameters. Patients with good change showed significantly superior local control than bad-change group (p=0.01, HR=0.22). In 113 stage III NSCLC patients with pre-radiation Kyn:Trp ratio, a trend that high baseline IDO1 activity was associated with short OS was observed(p=0.079). Conclusion: Favorable change of IDO1 activity during RT was associated with superior OS, PFS and local control. IDO1 activity is a promising biomarker for prognosis in stage III NSCLC patients.